2022
DOI: 10.1002/srin.202200151
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Ultrafine Acicular Bainite and Mechanical Properties of 3Cr2MnNiMo Mold Steel during Austempering

Abstract: Herein, the effect of austempering treatment on martensite/bainite multiphase microstructure evolution and mechanical properties of 3Cr2MnNiMo mold steel are investigated, and the mechanical properties are compared with the conventional quenching and tempering (QT) treatment. It indicated that the morphology of martensite/bainite can be effectively tailored by changing the austempering temperature. With the increase of temperature from 280 to 360 °C, the microstructure changes from tempered martensite + bainit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…Consistent with our observations, earlier researchers [15,40,44] reported that numerous bainitic ferrite-austenite interfaces reduced the mean free path for dislocation glide, hence leading to high strength. Similarly, the contribution of martensite to the strength was reported in earlier investigations [21,45,46].…”
Section: Experimental Findings and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with our observations, earlier researchers [15,40,44] reported that numerous bainitic ferrite-austenite interfaces reduced the mean free path for dislocation glide, hence leading to high strength. Similarly, the contribution of martensite to the strength was reported in earlier investigations [21,45,46].…”
Section: Experimental Findings and Discussionsupporting
confidence: 79%
“…As the term suggests, a stepped austempering process includes two stages of isothermal holding at different temperatures to exploit the advantages of both low-temperature and high-temperature austempering [18][19][20]. In case of a lowtemperature austempering, a benefit may be envisaged in terms of a larger driving force for austenite transformation due to greater under-cooling [21,22]. Owing to a higher driving force, CFB structure in a finer morphology with less austenite can be expected leading to higher strength levels.…”
Section: Introductionmentioning
confidence: 99%